The TIGIT+ T regulatory cells subset associates with nosocomial infection and fatal outcome in COVID-19 patients under mechanical ventilation - de Lima, Mikhael Haruo Fernandes; Machado, Caio Cavalcante; Nascimento, Daniele Carvalho; Silva, Camila Meirelles S.; Toller-Kawahisa, Juliana Escher; Rodrigues, Tamara Silva; Veras, Flavio Protassio; Pontelli, Marjorie Cornejo; Castro, Italo A.; Zamboni, Dario Simões; Filho, José-Carlos A.; Cunha, Thiago M.; et al. (Scientific reports, 2023)
The TIGIT + FOXP3 + Treg subset (TIGIT + Tregs) exerts robust suppressive activity on cellular immunity and predisposes septic individuals to opportunistic infection. We hypothesized that TIGIT + Tregs could play an important role in intensifying the COVID-19 severity and hampering the defense against nosocomial infections during hospitalization. Herein we aimed to verify the association between the levels of the TIGIT + Tregs with the mechanical ventilation requirement, fatal outcome, and bacteremia during hospitalization. TIGIT + Tregs were immunophenotyped by flow cytometry from the peripheral blood of 72 unvaccinated hospitalized COVID-19 patients at admission from May 29th to August 6th, 2020. The patients were stratified during hospitalization according to their mechanical ventilation requirement and fatal outcome. COVID-19 resulted in a high prevalence of the TIGIT + Tregs at admission, which progressively increased in patients with mechanical ventilation needs and fatal outcomes. The prevalence of TIGIT + Tregs positively correlated with poor pulmonary function and higher plasma levels of LDH, HMGB1, FGL2, and TNF. The non-survivors presented higher plasma levels of IL-33, HMGB1, FGL2, IL-10, IL-6, and 5.54 times more bacteremia than survivors. Conclusions: The expansion of the TIGIT + Tregs in COVID-19 patients was associated with inflammation, lung dysfunction, bacteremia, and fatal outcome.